"Contextualizing dispersoid evolution within the microstructure of MA956 using ion irradiation". (September 2021) - Getto, E.; Nathan, N.; McMahan, J.; Baker, B.; Taller, S.
Highlights: MA956 was irradiated with 5 MeV Fe ++ up to 200 dpa from 400 to 500 °C. Dispersoid evolution was attributed to Ostwald coarsening mechanism. Rate theory was used to explain dislocation behavior as a function of temperature. Voids nucleated on dispersoids only at 450 °C, 200 dpa. The complex behavior of dispersoids is influenced by the evolution of the other microstructure features. Abstract: Determining the microstructure evolution of oxide dispersion-strengthened (ODS) alloys is important for predicting the safety and structural integrity of fast reactors. In particular, understanding the co-evolution of dispersoids with the dislocation loops and network is critical for a comprehensive understanding of the microstructure response to radiation. Ion irradiations were performed on oxide dispersion strengthened MA956 with 5 MeV Fe ++ ions from 400 to 500 °C at doses ranging from 50 to 200 dpa. Characterization was performed primarily with scanning transmission electron microscopy and energy-dispersive x-ray spectroscopy to investigate the Y-Al-O dispersoids, voids and dislocations. Regardless of temperature, the dispersoids increased in diameter and decreased in number density, which was attributed to an Ostwald coarsening mechanism supported by calculations of the radiation enhanced diffusion and ballistic dissolution. MA956 demonstrated excellent void swelling resistance and did not form voids except at 450 °C, 200 dpa where voids nucleated upon dispersoids. The dislocation loop diameter was highest at 500 °C followed by 400 °C then 450 °C while number density tended to decrease with dose. The dislocation behavior was explained as a function of the evolving defect kinetics, utilizing rate theory to calculate point defect concentrations and the increasing diffusivity of vacancies. At 400 °C, the interstitials had high enough diffusivity to nucleate new loops but vacancies remained relatively immobile. At 450 °C, vacancies are able to annihilate interstitials due to non-negligible mutual recombination causing the decreased number density of loops. At 500 °C, vacancy and interstitials are both mobile where the interstitials coalesce to form larger loops and vacancies provide a pathway for solutes diffusing to and from dispersoids.